Priming Attitudes Towards Immigrants: Implications for Migration Research and Survey Design - Patrick Dylong; Paul Setzepfand; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using data from two representative and large-scale population surveys with more than 4000 participants, we investigate the effect of randomized priming interventions on attitudes towards immigrants. We document robust null effects of these interventions under two experimental settings, across two surveys and for a range of specifications. Our results suggest that (economic) attitudes towards immigrants are less sensitive to priming than previous research indicates. We thus provide (i) a reference point for settings in which intentional priming interventions are ineffective, and (ii) an upper bound for unintended priming effects. We argue that researchers should not be overly concerned about confounding priming effects when designing surveys to elicit attitudes towards immigrants.
Keywords: C83; C90; J15; F22; 330; attitudes towards immigration; priming; experimental design